The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/mar.21554
|View full text |Cite
|
Sign up to set email alerts
|

Impact of self‐brand connection on willingness to pay premium: Relevant mediators and moderators

Abstract: The purpose of this study is to investigate how self-brand connection in an interactive multi-actor single-brand retail context can lead to consumers' willingness to pay premium through the sequential mediation of brand attitudes (intransigent and flexible) and brand love. Study 1 shows that self-brand connection strengthens (weakens) consumers' intransigent (flexible) brand attitude, thereby increasing their brand love and willingness to pay price premium. Furthermore, consumers' high level of cynicism attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 105 publications
1
27
0
Order By: Relevance
“…General dimensions refer to the dimensions that are applicable to most fashion brands and have been verified ( Aaker, 1996 ). A set of examined general dimensions can provide guidance and structure for any customization brand, including perceived product quality, brand image, brand association, self-brand connection and brand culture ( Zeithaml, 1988 ; Keller, 1993 ; Aaker, 1996 ; Steenkamp et al, 2003 ; Maden, 2013 ; Cho et al, 2015 ; Ye et al, 2015 ; van der Westhuizen, 2018 ; Sarkar et al, 2021 ). Brand image and brand association are the most intertwined dimensions ( Cho and Fiore Ann, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…General dimensions refer to the dimensions that are applicable to most fashion brands and have been verified ( Aaker, 1996 ). A set of examined general dimensions can provide guidance and structure for any customization brand, including perceived product quality, brand image, brand association, self-brand connection and brand culture ( Zeithaml, 1988 ; Keller, 1993 ; Aaker, 1996 ; Steenkamp et al, 2003 ; Maden, 2013 ; Cho et al, 2015 ; Ye et al, 2015 ; van der Westhuizen, 2018 ; Sarkar et al, 2021 ). Brand image and brand association are the most intertwined dimensions ( Cho and Fiore Ann, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Strengthening the relationship between brand and self-concept helps improve self-brand connection, thereby increasing brand value ( Escalas and Bettman, 2003 ; Ye et al, 2015 ). For customization brands, the relationship can be fueled through products designed to represent consumers’ self-images and are subsequently expressed to others ( Escalas and Bettman, 2003 ; Saleh and Alotaibi, 2018 ; Lang et al, 2021 ; Sarkar et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, the perceived SBC is not uniform among consumers. Sarkar et al (2021) proposed that consumers with higher SBC develop an uncompromising attitude toward the focal brand, which is "not subject to switching to any other brand." On the other hand, those with a lower SBC perception have a more "flexible attitude toward the brand and are open to switching" in certain situations or "trying a new brand."…”
Section: Self-brand Congruence and Brand Pridementioning
confidence: 99%
“…Specifically, this study stream has focused on the building of a strong brand relationship as a long‐term strategy and outcome for the brand, and various studies have shown that this is built on the basis of positive brand behavior leading to positive consumer evaluations (MacInnis & Folkes, 2017; Park & John, 2018; Razmus et al, 2022). The long‐term relational focus has also shown to provide a better method of predicting buying behavior (Nyffenegger et al, 2015; Sarkar et al, 2021). In relation to CBRs in the context of a crisis, extant research has shown that firms with stronger relationships with their consumer's enjoy more positive response evaluations (Ozuem et al, 2021; Vázquez‐Casielles et al, 2010).…”
Section: Research Background and Hypothesesmentioning
confidence: 99%